The Determinants of Airline Operational Performance: An Empirical Study on Major World Airlines - KİRACI, Kasım; YAŞAR, Mehmet (Sosyoekonomi, 2020)
The air transport industry is a dynamic sector and operates in a dynamic environment. This situation leads to intense competition among airlines and, consequently, to a search for new methods to improve the operational performance. It is claimed that revealing the factors affecting the operational performance of airline companies will give them strategic advantages. Therefore, this study focuses on the factors that affect the operational performance of airlines, unlike previous studies in the literature. The aim of this study is to empirically examine the factors which determine the operational performance of airline companies. The operational data for the period between 1990 and 2017 of 52 airlines, which control more than 90% of the global air passenger transport industry, were analyzed using panel data analysis. The results of the study show that the number of passengers carried, the load factor, the number of flights made by the airlines, the rate of use of the aircraft and the amount of cargo carried by the airlines significantly affect their operational performance.
Keywords: Data envelopment; Economics; Panel data analysis; Havayolları; Airlines; Panel veri analizi; Efficiency; Alliances; Operational performance; Operasyonel performans; Productivity; Model; 9. Industry and infrastructure; 1. No poverty; 12. Responsible consumption; 8. Economic growth; 11. Sustainability